2015
DOI: 10.1007/s13311-015-0356-8
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Proliferation and Connectivity in PTEN-associated Autism Spectrum Disorder

Abstract: Germline mutations in PTEN, which encodes a widely expressed phosphatase, was mapped to 10q23 and identified as the susceptibility gene for Cowden syndrome, characterized by macrocephaly and high risks of breast, thyroid, and other cancers. The phenotypic spectrum of PTEN mutations expanded to include autism with macrocephaly only 10 years ago. Neurological studies of patients with PTENassociated autism spectrum disorder (ASD) show increases in cortical white matter and a distinctive cognitive profile, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 89 publications
(164 reference statements)
0
68
3
1
Order By: Relevance
“…Cowden syndrome (CS) is an uncommon, but difficult to recognize, disorder that results in hamartomas and an increased risk of breast, thyroid, endometrial, and renal cancers (Ngeow & Eng, ; Tan et al., ). The majority of CS patients have macrocephaly (Mester, Tilot, Rybicki, Frazier, & Eng, ), and there is a subset of patients with autism spectrum disorder and macrocephaly with germline PTEN (MIM# 601728) mutations (Butler et al., ; Tilot, Frazier, & Eng, ). The CS susceptibility locus was initially mapped to 10q23.3 (Nelen et al., ) and 9‐exon PTEN was subsequently identified as the predisposition locus (Li & Sun, ; Liaw et al., ; Lynch et al., ).…”
Section: Pten* Intronic Variation and Resulting Rna Alteration With Pmentioning
confidence: 99%
“…Cowden syndrome (CS) is an uncommon, but difficult to recognize, disorder that results in hamartomas and an increased risk of breast, thyroid, endometrial, and renal cancers (Ngeow & Eng, ; Tan et al., ). The majority of CS patients have macrocephaly (Mester, Tilot, Rybicki, Frazier, & Eng, ), and there is a subset of patients with autism spectrum disorder and macrocephaly with germline PTEN (MIM# 601728) mutations (Butler et al., ; Tilot, Frazier, & Eng, ). The CS susceptibility locus was initially mapped to 10q23.3 (Nelen et al., ) and 9‐exon PTEN was subsequently identified as the predisposition locus (Li & Sun, ; Liaw et al., ; Lynch et al., ).…”
Section: Pten* Intronic Variation and Resulting Rna Alteration With Pmentioning
confidence: 99%
“…Initial cases were suggestive of an association (Delatycki et al 2003;Eng 2003) and subsequent small cohort studies identified an enriched number of PTEN mutations in ASD cases with macrocephaly (PTEN-ASD) (Butler et al 2005;Buxbaum et al 2007). Later cohorts with larger samples of individuals with ASD and/or ID (neurodevelopmental delay) found similar proportions of PTEN mutations (Herman et al 2007;Orrico et al 2009;Varga et al 2009;McBride et al 2010;Hobert et al 2014), resulting in a weighted average of 17% of macrocephalic ASD and translating to approximately 2% of all ASD cases (Tilot et al 2015). Approaching ASD prevalence from the PTEN mutation angle, recent case series have suggested that 25%-50% of children with PTEN mutations are identified with ASD (Hansen-Kiss et al 2017;Ciaccio et al 2018).…”
Section: Pten and Asdmentioning
confidence: 98%
“…A subset of variants in the PTEN gene, particularly those that alter residues outside of the phosphatase domain and are associated with cancer, may act in a dominant negative fashion [Papa et al, ]. While mouse and in vitro human cell models have demonstrated the efficacy of mTOR inhibitors in reversing part of the phenotypic consequences of PTEN haploinsufficiency, mostly on its canonical effects on cell growth and number [Krymskaya and Goncharova, ; Tilot et al, ], their efficacy on the non‐canonical “moonlighting” functions of PTEN , such as chromatin and transcriptional activity, remains unclear. This has implications for therapeutic outcomes, since inhibiting the effects from excessive PI3K pathway activity may not be sufficient or may not target other aspects of PTEN function that extend beyond the PI3K‐AKT‐mTOR signaling pathway, including its functions in the nucleus.…”
Section: Pten Hamartoma Tumor Syndrome (Phts)mentioning
confidence: 99%